Decision making in breast cancer treatment: a qualitative inquiry - Mohd Shariff, Zalilah; Mansor, Ahmad Zamri; Muhamad, Mazanah (Universiti Putra Malaysia Press, 2008)
For breast cancer patients, making decisions are integral to cancer diagnosis, treatment and prevention of recurrence. In order to make these decisions, cancer patients require appropriate and relevant information or guide. These decisions can also be influenced by external and internal factors. To get an insight into decision making related to breast cancer treatment from the perspective of breast cancer patients and survivors, a series of focus group discussions (FGD) were conducted with 36 informants of the Chinese and Malay ethnicities. The informants were recruited from breast cancer support groups in the northern, central, southern and eastern regions of Peninsular Malaysia. The following research questions guided the FGD. These were (1) Who make (s) decision on cancer treatments?, (2) What guide (s) the decision making?, and (3) What influence (s) the decision? For most informants, the primary decision maker in their cancer treatment was themselves. However, these decisions were made upon advice and support from the physicians, family members and friends. The informants stated that information from physicians, family members, friends, internet, books and magazines also served as guidance to decision making on cancer treatment and management. Following the physicians’ advice, having the knowledge on breast cancer, taking care of family members and wanting to live longer to fulfil personal goals were also mentioned by these informants as factors which had influenced their treatment decision making. Further research using a quantitative approach is therefore recommended to confirm the findings of this study.